Analisis Efek Ratcheting Pada Pendapatan Asli Daerah Terhadap Belanja Daerah di Kabupaten/ Kota di Provinsi Sumatera Barat, Riau dan Jambi Tahun 2015-2018 - Chaterine Anjeli; Erly Mulyani (Universitas Negeri Padang, 2020)
Knowing the effect of local revenue on regional expenditures and knowing the effect of ratcheting on the relationship between local revenue and regional expenditures for district/city governments in West Sumatra, Riau and Jambi are the objectives of this study. The population in this study were districts/cities in West Sumatra, Riau and Jambi which consisted of 19 districts/cities, districts/cities in West Sumatra 12 districts/cities in Riau and consisted of 11 districts/cities in Jambi in 2015-2018. Multiple regression method with SPSS software used in this study. The results of this research are, firstly, it shows that the local original income variable has a significant positive effect on regional spending, while the ratcheting effect variable as moderating weakens the relationship between regional original income and regional spending.